137Cs inventories in soil in the Qaidam Basin, Tibetan Plateau - Bian, Kai; Wang, Cuiping; Shen, Yulong (Frontiers in Environmental Science, 2023)
This paper presents measurements of cesium-137 (137Cs) in the Qaidam Basin during 2019 with 39 soil samples across the landscape. The aim here is to use the results of 137Cs inventories for the Qaidam Basin to subsequently estimate soil wind erosion. The 137Cs inventories in the surface soil vary from lower limit detection (LDD) to 1,072 Bq m−2, with a mean of 266 Bq m−2. Overall, the 137Cs inventories in the Qaidam Basin decreases from southeast to northwest. The highest 137Cs inventories was found in farmland, and the lowest was found in Gobi. Wetlands had higher 137Cs inventories than their neighboring sites.